Aeroallergen Avoidance: Updated Evidence and How to Advise Patients (Actualité en allergologie et en immunologie au Canada, 2023)
Allergic rhinitis (AR) is highly prevalent in Canada, affecting approximately 20–25% of the population. Asthma is estimated to affect approximately three million Canadians, and between 12% and 25% of Canadian children. Approximately two-thirds of individuals with asthma are allergic to aeroallergens, and these allergens act as triggers for asthma exacerbations. Overall, approximately 7.7 million individuals were affected by aeroallergens in Canada in 2016. High concentrations of ambient aeroallergens, including tree pollen and fungal spores have been associated with increased risk of premature birth, myocardial infarction (MI) and asthma-related Emergency Department visits and hospitalizations in cities across Canada. This demonstrates that nation-wide aeroallergen counts are associated with severe signs and symptoms.Children exposed to various indoor allergens are placed at an increased risk of developing asthma in later life, with sensitization in these individuals being a strong predictor of disease morbidity. Common indoor exposures for infants include house dust mite, pet, cockroach, mould, and rodent allergens. Sensitization to at least one indoor allergen has been demonstrated to be present in nine of every ten children hospitalized with asthma.It has been noted that more than 90% of children worldwide breathe polluted air. While the impact of climate change on aeroallergen exposure is not fully understood, there is increasing evidence that it may have an impact on outdoor aeroallergens and, by extension, asthma control in children. Global warming has been projected to influence the duration and intensity of pollen seasons, and may lead to increased pollen production, prolonged pollen seasons, and increased pollen protein allergenicity.The changing weather patterns including rainfall and wind may cause pollen species to reach environments in which they had not previously been present, contributing to a shift in geographic pollen distributions.